2015
DOI: 10.3357/amhp.3938.2015
|View full text |Cite
|
Sign up to set email alerts
|

Hypobaric Hypoxia: Effects on Contrast Sensitivity in High Altitude Environments

Abstract: The study demonstrated that hypoxia and variations of atmospheric pressure may produce corneal edema, including changes of CCT and, correlatively, CS reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…The higher contrast sensitivity, which was 1.5 ~ 3 Cpd, was decreased signi cantly when the level was raised to 4500 m. This indicated that the small cell channel dealing with the lower spatial frequency was more sensitive to hypoxia. Our results was somewhat in accordance with that of Pescosolido N et al, who found that Hypobaric hypoxia conditions in pilots reduced contrast sensitivity (1.95 log to 1.05 log) in a statistically signi cant result [12] . Besides, et al also argued that the contrast sensitivity signi cantly increased after 5, 10 and 15 min of hypoxic exposure in their study [13] .…”
Section: Discussionsupporting
confidence: 94%
“…The higher contrast sensitivity, which was 1.5 ~ 3 Cpd, was decreased signi cantly when the level was raised to 4500 m. This indicated that the small cell channel dealing with the lower spatial frequency was more sensitive to hypoxia. Our results was somewhat in accordance with that of Pescosolido N et al, who found that Hypobaric hypoxia conditions in pilots reduced contrast sensitivity (1.95 log to 1.05 log) in a statistically signi cant result [12] . Besides, et al also argued that the contrast sensitivity signi cantly increased after 5, 10 and 15 min of hypoxic exposure in their study [13] .…”
Section: Discussionsupporting
confidence: 94%
“…The recorded levels of SaO 2 were lower at PH when compared to both PV and CM, in accordance with literature. [22] The decrease in SaO 2 is explained by the fall of partial pressure of oxygen in the breathing air at high altitudes. Although the percentage of oxygen in inhaled air is constant at different altitudes, the fall in atmospheric pressure at higher altitudes decreases the partial pressure of inhaled oxygen and hence the driving pressure for gas exchange in the lungs.…”
Section: Correlation Between Iop and Systemic Parametersmentioning
confidence: 99%
“…Exposure to hypoxia can have a significant effect on human vision, manifesting as changes in colour discrimination (Connolly et al, 2008), reduction in dark adaptation (Kobrick and Appleton, 1971), and loss of contrast sensitivity (Pescosolido et al, 2015), with the changes being more evident in low light environments (Connolly et al, 2008). In contrast, high altitude has no effect on visual acuity (Bosch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%